Community Service Order Punishment: Alternatives in The Criminal Law System From Maqāṣid al-Sharīʿah Perspective - Sirait, Adi Syahputra; Syahnan, Mhd.; Panjaitan, Budi Sastra (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to analyze Community Service Order (CSO) punishment within the criminal law system through the lens of Islamic law, using a multi-dimensional approach. As an alternative to detention, CSO punishment is expected not only to achieve the rehabilitation of offenders but also to provide broader benefits to society. This study explores how the concept of maqāṣid al-sharīʿah with a multi-dimensionality approach—which includes social, economic, and cultural analysis—by looking at the relevance of maqāṣid al-sharīʿah and a comprehensive view of the concept of community service order punishment to achieve a balance between justice, rehabilitation, and social welfare. A multi-dimensionality approach is used to study community service order punishment from social, economic and cultural aspects. The results of the study show that Community Service Order Punishment are not only in line with the principles of maqāṣid al-sharīʿah, but also have the potential to increase the effectiveness of the rehabilitation of perpetrators, reduce detention costs, and increase the positive contribution of perpetrators to society. This study concludes that Community Service Order Punishment can be a more humane and effective alternative in the criminal law system, which is in line with Islamic values and supports the welfare goals of society as a whole.